BRAND BENEFIT POSITIONING STRATEGY AND REPURCHASE INTENTION OF CONSUMERS OF FOOD AND BEVERAGES BRANDS IN RIVERS STATE, NIGERIA - Dr Lawrence Amadi (Scholar Express Journals, 2022)
The study investigated the effect of brand benefit positioning strategy on repurchase intention of customers towards food and beverage products in Rivers State, Nigeria. The descriptive survey research gathered data from 490 entrepreneurs and customers who patronise SMEs in Port Harcourt. A well structured questionnaire containing 8 items, with five demographic items was used to generate data from the respondents. The reliability analysis of the instrument with Chronbach Alpha produced a value of 0.775, which confirmed the consistency of the research items. The inferential statistics showed that brand benefit positioning strategy had significant predictive capabilities repurchase intentions. In conclusion, brand benefit positioning strategies had significant statistical influence on repurchase intentions towards food and beverage brands in Rivers State. Precisely, 81.5%, changes in customers’ repurchase intentions were significantly predicted by brand benefits. Therefore, this study recommended that food and beverage manufacturing companies should focus on enhancing brand benefits accruable to consumers to enhance repeat patronage
Keywords: Brand Benefit Capability; Repurchase Intention; Food and Beverages SMEs